Pembibitan Tanaman Porang (Amorphophallus Muelleri Blume) dengan Model Agroekosistem Botol Plastik - Ganjari, Leo Eladisa (Widya Warta, 2014)
This study is aimed to determine (1) the ability of bulbil to produce shoots, (2) the growth of Porang planted using Agroecosystem Model of Plastic Bottles (AMPB), and (3) the relevance of AMPB in the effort of Porang breeding. The research was conducted in January up to September 2012 in Madiun. It made use of plastic bottles as the medium for the growth of bulbil shoots and the growth of Porang plant, which is referred to as Agroecosystem Model of Plastic Bottles. The bulbil used in this study was obtained from the forest of Saradan, Madiun, East Java. The seedlings which sprouted from the single bulbil were planted and let grow for three months with Agroecosystem Model of Plastic Bottles. The results showed that in the frog tubers more than one bud could grow. The study also found that there were six variations of the number of bulbil shoots namely, 1, 2.3, 5, and 12 per frog tuber. Porang seedlings from bulbil could grow well with Agroecosystem Model of Plastic Bottles (AMPB). During the three month growth, the plant grew an average of 39.40 cm high, the average of canopy diameter = 30.00 cm and of trunk diameter = 0.85 cm. The stem tuber obtained weighed an average of 120.42 grams with the average diameter = 5.71 cm. Bulbil was produced in both the middle and branch leaves. The middle bulbil weighed an average of 1.33 grams with the average diameter = 1.52cm. The branch bulbil weighed an average of 0.19 grams with the average diameter = 0.59 cm. Planting Porang with Agroecosystem Model of Plastic Bottles (AMPB) showed normal growth. Thus, the breeding of Porang with the modelis still considered relevant.